Mechanism of Rehabilitation Against Narcotics Abuse by Children - Ainun Kasim (Estudiante Law Journal, 2021)
This study aims to determine and analyze how the implementation of Article 54 of Law Number 35 of 2009 concerning Narcotics, which is related to rehabilitation, especially for children who are not old enough. Then also to identify the efforts and obstacles faced in the process of implementing the rehabilitation.This research is classified as empirical research, namely research using field data in the form of interviews with parties directly related to the object under study. The results of the study show that Article 54 of Law Number 35 of 2009 concerning Narcotics related to rehabilitation has not reached the maximum point in its implementation in Gorontalo Province. Rehabilitation in its implementation is hampered due to the lack of adequate facilities and infrastructure. Rehabilitation of children also becomes a little more difficult because of the difficulty of creating comfort for children while undergoing rehabilitation which ultimately causes the child and the child's parents to be less cooperative in the implementation of rehabilitation. Therefore,